Pengaruh Ukuran Perusahaan, Likuiditas, Leverage Dan Profitabilitaspada Kelengkapan Pengungkapan Laporan Keuangan(Studi Empiris Padaperusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Bei) Tahun 2012-2013) - Ariyanti, Tutik, Drs. Agus Endro Suwarno, M.Si (2015)
In the conduct of activities in the capital markets, investors took the decision from the information received.As one of many efforts to attract the investors, The Company has been charged to disclose financial report. The demands the higher due to tight competition in the business world so the company has been charged to disclose financial report more transparently so that it will be more helpful investors in decision-making to anticipate the condition of being it is often altered with the development of existing. This research aims to understand the influence of the size of company, liquidity, leverage and profitability in the completeness of the disclosure of financial reports with empirical studies at manufacturing firm registered in Bursa Efek Indonesia (Indonesia Stock Exchange) in 2012 to 2013. A population that used in this research was the rest of the company manufacturing listed on Bursa Efek Indonesia (Indonesia Stock Exchange) in 2012 to 2013. A method of the sample collection is purposive by means of sampling in accordance with the criteria have been determined. The total sample is 162 companies. Analysis method used in this research is double linear regression. From this research obtained the conclusion that an impact on the completeness of variable size company financial disclosure report, while the ratio of the current variables, debt to equity and return on assets did not influence on the financial report. The regression equation is obtained was that KPLK =0,498+0,023 SIZE + 0,001CR + 0,007 DER - 0,082 ROA+e. The regression coefficient (R2) is 0,218 which means 21,8% the completeness of the disclosure on a financial report affected by the independent variable, while the rest of 78.2 % influenced by other variables that is not discussed in this research. Keyword: Completeness financial disclosure report, The size of the company,liquidity, leverage, profitability.